Germinação do coquinho-azedo: aspectos morfoanatômicos e fisiológicos - Natalia Cristina Correa de Oliveira (2012)
Coquinho-azedo (Butia capitata) is a palm tree native of cerrado, which presents great economic importance due to the exploitation of its fruits, as well as its ornamental use. However, this species is threatened by predatory extractivism, a fact that is compounded due to the difficulty of germination of their seeds, thus limiting its commercial exploitation. In the family Arecaceae is commonly observed the low rate of germination of their seeds, this factor may be related to dormancy, which often is associated with a rigid wrap, which make difficult the imbibitions and the entry and exit of gases, as well as the immaturity of embryo. Thus, the germinative process follows a triphasic pattern of water imbibitions, being the first a purely physical process of entry and exit of water in the seed. The second already represents the activation of metabolism, while the third characterizes germination or primary root protrusion. However, not always the process of removal of the endocarp and operculum present positive results of germination, requiring further studies in order to understand the germinative process, as the mobilization of the embryonic reserves and the establishment of parameters about the type of dormancy established in the seed.